Personal protective equipment solution for UK military medical personnel working in an Ebola virus disease treatment unit in Sierra Leone. Issue 1 (May 2017) - Reidy, P.; Fletcher, T.; Shieber, C.; Shallcross, J.; Towler, H.; Ping, M.; Kenworthy, L.; Silman, N.; Aarons, E.
Summary: The combination of personal protective equipment (PPE) together with donning and doffing protocols was designed to protect British and Canadian military medical personnel in the Kerry Town Ebola Treatment Unit (ETU) in Sierra Leone. The PPE solution was selected to protect medical staff from infectious risks, notably Ebola virus, and chemical (hypochlorite) exposure. PPE maximized dexterity, enabled personnel to work in hot temperatures for periods of up to 2 h, protected mucosal membranes when doffing outer layers, and minimized potential contamination of the doffing area with infectious material by reducing the requirement to spray PPE with hypochlorite. The ETU was equipped to allow medical personnel to provide a higher level of care than witnessed in many existing ETUs. This assured personnel working as part of the international response that they would receive as close to Western treatment standards as possible if they were to contract Ebola virus disease (EVD). PPE also enabled clinical interventions that are not seen routinely in West African EVD treatment regimens, whilst providing a robust protective barrier. Competency in using PPE was developed during a nine-day pre-deployment training programme. This allowed over 60 clinical personnel per deployment to practice skills in PPE in a simulated ETU and in classrooms. Overall, the training provided: (i) an evidence base underpinning the PPE solution chosen; (ii) skills in donning and doffing of PPE; (iii) personnel confidence in the selected PPE; and (iv) quantifiable testing of each individual's capability to don PPE, perform tasks and doff PPE safely.